Design and implementation of a compact highly efficient 472kHz radio frequency generator for electrosurgery - Eberhardt, Gerald M., author; Collins, George J., advisor; Siegel, Howard Jay, committee member; Chen, Thomas Wei, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2011)
This thesis explores the utilization of modern design practices and advance technologies to reduce the size of traditional 472kHz radio frequency generators used for electrosurgery. Achieving the reduced size requires an innovative approach to increase the overall efficiency to lower the internal heat dissipation allowing the overall package size to shrink. This thesis covers the selection and design process to achieving the final topology of an innovative approach utilizing a variation of the Class-D amplifier to produce a resonance type power saturation amplifier. While using a high-efficiency power source to control the amplifier voltage rails, and to control the amplitude of the output signal will produce a sinusoidal power source capable of driving a radio frequency surgical scalpel.
Keywords: 472kHz; generator; electrosurgery